관망에서의 소독부산물 변화와 관련 영향인자들의 상관관계 분석 - 송영일(Young Il Song); 안수나(Suna Ann); 안성윤(Seoungyun Ann); 서대근(Daeguen Seo); 조혁진(Hyukjin Cho); 이재성(Jaesung Lee); 최일환(Ilwhan Choi); 신창수(Changsoo Shin); 이희숙(Hee Suk Lee) (Daehan hwan'gyeong gonghag hoeji, 2016)
The distributed systems managed by K-water were surveyed to study the characteristic of disinfection-by-product (Trihalomethans & Haloacetic acids) formation and the correlations between the concentrations of disinfection-by-product and physico-chemical parameters. Five distribted system were selected according to their water ages and the degree of deterioration of their pipelines. Total seven items including Trihalomethans (THMs), Haloacetic acids (HAAs), BDOC, DOC, pH, chlorine residual, and temperature were analysed in monthly basis. The concentration of organic matter were increased according to water age and pipeline deterioration in this study. The coefficient of determination between the decline of residual chlorine and the increase of water age was revealed as high. Also, the coefficient of determination between the decline rate of residual chlorine and the increase of the Trihalomethans concentration were studied as high. Furthermore the longer water age is the bigger the effect on Trihalomethans formation and temperature. However, the coefficient of determination between the concentraion of Haloacetic acid and water age, residual chlorine, and temperature were revealed as low in this study. 수돗물 공급과정에서의 소독부산물 발생현황과 이와 관련된 수질 인자와의 상관성을 조사하여 소독부산물 발생특성을 규명하고자 K-water에서 관리하는 정수장의 수돗물 공급과정 5개 계통에 대하여 조사를 실시하였다. 수돗물 공급과정에서의 공급계통별 Water age 및 노후관 공급계통을 구분하여 조사대상을 선정하였으며, 소독부산물인 트리할로메탄 (THMs) 및 할로아세틱에시드 (HAAs), 유기물 항목으로서 BDOC 및 DOC를 포함하여 7개 항목에 대해 월 1회 조사하였다. 조사결과 노후관계통 및 Water age가 길수록 공급과정 내 유기물 농도가 높아지는 경향성을 확인할 수 있었다. 소독부산물과 관련 영향인자들의 상관관계를 분석한 결과 계통별 잔류염소 감소와 Water age간 상관관계가 매우 높은 것으로 나타났다. 또한 Water age와 THMs 생성간의 결정계수값이 매우 높아 THMs 생성에 Water age가 중요한 인자임을 알 수 있었다. 잔류염소 감소율이 THMs 증가에 미치는 영향 또한 매우 높게 나타났으며, Water age가 길어질수록 수온과 THMs 생성에 미치는 영향은 증가하는 것으로 나타났다. 이와 반면 HAAs는 THMs와는 달리 Water age, 잔류염소, 수온과의 상관관계 조사결과 결정계수 값이 낮게 나타났다.